DNA methylation and imprinting in plants: machinery and mechanisms. (4th March 2017) - Satyaki, P. R. V.; Gehring, Mary
Abstract: Imprinting is an epigenetic phenomenon in which genes are expressed selectively from either the maternal or paternal alleles. In plants, imprinted gene expression is found in a tissue called the endosperm. Imprinting is often set by a unique epigenomic configuration in which the maternal chromosomes are less DNA methylated than their paternal counterparts. In this review, we synthesize studies that paint a detailed molecular portrait of the distinctive endosperm methylome. We will also discuss the molecular machinery that shapes and modifies this methylome, and the role of DNA methylation in imprinting.